Marriage Guardianship Law for Women in Islamic Jurisprudence, KHI and Supreme Court Decisions (Analysis of Religious Court Judges' Perceptions) - Akbar, Ahmad Ali (Jurnal Hukum Khaira Ummah, 2025)
This study aims to understand how Religious Court judges interpret the law on female marriage guardianship in the KHI and jurisprudence. This empirical study involved judges throughout Indonesia through an online survey for 10 months (October 2021 – July 2022) to analyze the legal discovery methods used by judges in deciding related cases. This study analyzed data from 52 religious judges who were determined using purposive sampling. Data collection methods included in-depth interviews, questionnaires, and document studies. Qualitative data analysis with a descriptive-analytical approach was used to describe and interpret the research findings. Research on marriage guardianship for women in the KHI and Supreme Court Decision Number 002 K/AG/1985 shows that there are three main understandings among Religious Court judges: a) marriage guardianship is absolutely necessary for all women; b) marriage guardianship is only mandatory for women under 21 years of age; and 3) the obligation of marriage guardianship can be reviewed based on the benefit and does not deviate from the opinions of the Islamic schools of thought. This difference in understanding arises due to the diverse methods of interpretation of the related articles (19, 71, 107) of the KHI and the Supreme Court Decision. Although the majority of respondents agree that the application of the Supreme Court Decision is more in line with PERMA Number 3 of 2017, the majority of Religious Court judges still believe that the rule of marriage guardians as a pillar of marriage that must be fulfilled for all women is more relevant to be applied in Indonesia today.